MANAGEMENT OF CONJUNCTIVAL MELANOMA ARISING FROM PRIMARY ACQUIRED MELANOMA (PAM) : A CASE REPORT: Poster Presentation - Case Report - Ophthalmologist - DYAH TJINTYA SARIKA; Hernawita Suharko (Majalah Oftalmologi Indonesia, 2023)
Introduction : Conjunctival melanoma (CMM) is a rare but potentially a life threatening ocular malignancy. It is an aggressive pigmented tumor and the recurrence rate may be as high as 51% over 10 years.1,2 Surgical wide local excision of the tumour and cryotherapy are current standard treatment of CMM.3,4 The purpose of this case is to report our successful management of conjunctival melanoma using wide excision and cryotherapy. Case Illustration : A 67-year-old man who presented to our hospital with a large, pigmented lesion arising from inferior and superior fornix conjunctiva in his left eye since 6 months ago. On examination, a massive pigmented tumor sized 25 x 10 x 15 mm, protruding from inferior fornix conjunctiva and sized 7 x 5x 3 mm arising from superior fornix conjunctiva of left eye. The mass was excised with 3 mm free margin from the tumour border confirmed with negative frozen section and followed by cryotherapy and conjunctival reconstruction using oral mucous graft. Histopathology confirmed with invasive conjunctival melanoma arising in PAM with severe atypia and no lymphovascular and perineural metastasis Discussion : Two months after we performed wide excision, cryotherapy and oral mucous graft, no recurrence and conjunctival necrosis at primary site were reported. Conclusion : A local wide excision with ‘no touch technique’, cryotherapy and oral mucous graft confirmed with negative frozen section are the mainstay treatment of CMM and has achieved satisfying functional outcomes. Since the high recurrence rate of CMM, we have to close follow up for the next 3 years